ANALISIS PENYAJIAN LAPORAN KEUANGAN PEMERINTAHAAN KABUPATEN TULUNGAGUNG - Ramadhan, Rachmat Sandy; Rustam, Akie Rusaktiva (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study  aims to determine the  presentation of financial statements  has been fully implemented Tulungagung follow SAP PP No. 71 Year 2010 annex II. This research is descriptive qualitative. The data in  this study were obtained  by means of  field studies  is through  interview, observation, and documentation. The process of  data analysis  using  qualitative  methods,  which include  analysis  of financial  statement presentation  system  that  currently  run  vBulletin  district government as outlined in the accounting policies as compared with SAP No.. 71 (Annex II). The results of this study showed that based on its Financial Statements components  BPKAD  Tulungagung  have followed  SAP  No..  71  of 2010 (Appendix II). Yet the budget realization report, the presentation of the financing is still not converted post by SAP and still follow the classification or labeling by post or by post Permendagri financing district government budget in vBulletin. Keywords:   Presentation of Financial Statements, SAP PP  No 71, Region Tulungagung.